2009
DOI: 10.1897/08-518.1
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic cytotoxic effect of tetrachlorocatechol and sodium azide in Escherichia coli: Toxicity, metabolism, and mechanistic aspects

Abstract: Pentachlorophenol (PCP) is used in industrial and domestic applications, including as a biocide and a wood preservative. Metabolism of PCP undergoes oxidative dechlorination, forming tetrachlorocatechol (TCC) and tetrachlorohydroquinone (TCHQ). Both sodium azide (NaN(3)) and TCC appear naturally in soil. None of them are cytotoxic by themselves or facilitate autooxidation. Here, we show that their combination leads to synergistic cytotoxicity (>6 log bacterial killing) to Escherichia coli. The rate of oxygen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Our previous work showed that the reaction between TCC and NaN 3 was accompanied with enhanced oxygen consumption (from 100 to 60 %, Figure 3 A: Control) and the formation of O-tetrachlorosemiquinone anion radical (O-TCSQC À ) and other semiquinone radicals (SQC À ; Figure 3 C), which were considered to be the reactive and toxic species responsible for cell death. [15] We found that both the oxygen consumption and semiquinone radicals generation (as monitored by direct ESR) was inhibited by 2,9-Me 2 OP in a dose-dependent manner. When the molecular ratio of [2,9-Me 2 OP]/[TCC] = 1:1, no oxygen consumption was observed and the semiquinone radicals relative value was reduced to the base line, indicating that the reaction between TCC and NaN 3 was completely inhibited by 2,9-Me 2 OP (Figure 3 A and D).…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…Our previous work showed that the reaction between TCC and NaN 3 was accompanied with enhanced oxygen consumption (from 100 to 60 %, Figure 3 A: Control) and the formation of O-tetrachlorosemiquinone anion radical (O-TCSQC À ) and other semiquinone radicals (SQC À ; Figure 3 C), which were considered to be the reactive and toxic species responsible for cell death. [15] We found that both the oxygen consumption and semiquinone radicals generation (as monitored by direct ESR) was inhibited by 2,9-Me 2 OP in a dose-dependent manner. When the molecular ratio of [2,9-Me 2 OP]/[TCC] = 1:1, no oxygen consumption was observed and the semiquinone radicals relative value was reduced to the base line, indicating that the reaction between TCC and NaN 3 was completely inhibited by 2,9-Me 2 OP (Figure 3 A and D).…”
Section: Resultsmentioning
confidence: 72%
“…− ) and other semiquinone radicals (SQ . − ; Figure 3 C), which were considered to be the reactive and toxic species responsible for cell death 15. We found that both the oxygen consumption and semiquinone radicals generation (as monitored by direct ESR) was inhibited by 2,9‐Me 2 OP in a dose‐dependent manner.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations